A cross-level model of team-level psychological capital (PsyCap) and individual- and team-level outcomes. (11th March 2021) - Dawkins, Sarah; Martin, Angela; Scott, Jenn; Sanderson, Kristy; Schüz, Benjamin
Abstract: Psychological capital (PsyCap) is a higher-order construct reflecting the psychological resources of hope, efficacy, resilience and optimism. This study adopted a multilevel approach to investigate relationships between team-level PsyCap and team- and individual-level outcomes. We also compared two compositional models of aggregation to represent team-level PsyCap. Findings revealed significant associations between team-level PsyCap and team- (performance and satisfaction) and individual-level (job satisfaction, turnover intent) outcomes, particularly when a referent-shift model of aggregation was employed. We also investigated PsyCap strength to explore the degree to which team member consensus regarding PsyCap perceptions may moderate these relationships. We found that team PsyCap strength had a significant influence in the prediction of most outcomes. Our findings emphasize the importance of fostering team-level positivity, as the benefits of team-level PsyCap can operate at both the individual and team level. Theoretical and practical implications of the findings are discussed, along with avenues for future research.